2008
DOI: 10.1200/jco.2006.10.4505
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Results in Pathologic Stage C Prostate Cancer From a Southwest Oncology Group Trial Comparing Radical Prostatectomy Alone With Radical Prostatectomy Plus Radiation Therapy

Abstract: The addition of RT to surgery resulted in more frequent urination, as well as early report of more bowel dysfunction, although bowel function differences disappeared over the 5-year period. The addition of RT did not negatively impact ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 37 publications
5
78
1
3
Order By: Relevance
“…Some studies have reported that RT after RP has minimal long-term urinary consequences. 11 In contrast, other studies have reported a higher morbidity of subsequent RT after RP. The EORTC trial 22911 showed 11% more UAEs (any grade) at 10 years follow-up, in men with RP + RT, compared to RP alone 12 .…”
Section: Accepted Manuscriptcontrasting
confidence: 42%
“…Some studies have reported that RT after RP has minimal long-term urinary consequences. 11 In contrast, other studies have reported a higher morbidity of subsequent RT after RP. The EORTC trial 22911 showed 11% more UAEs (any grade) at 10 years follow-up, in men with RP + RT, compared to RP alone 12 .…”
Section: Accepted Manuscriptcontrasting
confidence: 42%
“…Therefore, these results may not be applicable to current clinical practice. 30 Moinpour et al 31 reported on prospective assessments of the QOL outcomes for the SWOG 8794 randomized adjuvant radiation therapy trial. In their report on 217 patients, who completed a HealthRelated Quality-of-Life (HRQOL) questionnaire after surgery and before radiation therapy, the researchers found no difference in erectile functioning between 107 patients who underwent radical prostatectomy alone and those who had additional radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have more thoroughly addressed the HRQOL effects of adjuvant EBRT following RP. 19 With regard to HRQOL assessments, the UCLA PCI is relatively insensitive to urinary irritative symptoms often seen after radiotherapy and does not assess hormonal symptoms. 21 Other HRQOL surveys, such as the EPIC, may have provided more information, but in terms of sexual and urinary domains the EPIC and the UCLA PCI have been shown to correlate well.…”
Section: Discussionmentioning
confidence: 99%